2021
DOI: 10.3389/fimmu.2021.758288
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptomic Analysis Reveals a Tumor-Reactive T Cell Signature Associated With Clinical Outcome and Immunotherapy Response In Melanoma

Abstract: The infiltration of tumor-reactive T cells in the tumor site is associated with better survival and immunotherapy response. However, tumor-reactive T cells were often represented by the infiltration of total CD8+ T cells, which was confounded by the presence of bystander T cells. To identify tumor-reactive T cells at the cancer lesion, we performed integration analyses of three scRNA-seq data sets of T cells in melanoma. Extensive heterogeneous functional states of T cells were revealed in the tumor microenvir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 65 publications
0
14
0
Order By: Relevance
“…We analyzed its predictive Additionally, we investigated the differences of immune checkpoints expression. The tumor responsiveness score, 20 T cell CYT score 21 and Th1/IFN score 22,23 were assessed in the high-and low-risk groups to learn about their responsiveness toward immunotherapy. (UMI) and mRNA is illustrated in Supplementary Figure S1A.…”
Section: Different Patterns Of Tmb Tme Immunotherapy Responsiveness A...mentioning
confidence: 99%
“…We analyzed its predictive Additionally, we investigated the differences of immune checkpoints expression. The tumor responsiveness score, 20 T cell CYT score 21 and Th1/IFN score 22,23 were assessed in the high-and low-risk groups to learn about their responsiveness toward immunotherapy. (UMI) and mRNA is illustrated in Supplementary Figure S1A.…”
Section: Different Patterns Of Tmb Tme Immunotherapy Responsiveness A...mentioning
confidence: 99%
“…Single-cell sequencing (scRNA-seq) has been used to perform an in-depth analysis of the T-cells present within CM and UM (e.g. (Durante et al, 2020;Tirosh et al, 2016;Yan et al, 2021)) but an equivalent comprehensive analysis of B-cells using this technology (1) (Helmink et al, 2020), while another used gene sets to identify the presence of activated, immature and memory B-cells and more rarely, plasma cells in melanomas (Cabrita et al, 2020).…”
Section: Phenot Ype Of B -Cell S Infiltr Ating Mel Anomamentioning
confidence: 99%
“…Single‐cell sequencing (scRNA‐seq) has been used to perform an in‐depth analysis of the T‐cells present within CM and UM (e.g. (Durante et al, 2020; Tirosh et al, 2016; Yan et al, 2021)) but an equivalent comprehensive analysis of B‐cells using this technology has not been completed, to date. One recent study used k‐means clustering of scRNA‐seq data to split B‐cell TILs into four clusters, characterised by user‐defined phenotypes based on markers (1) switched, activated IgD − ; (2) plasma cells; (3) unswitched IgD + and (4) switched, activated IgD − , with unique markers relative to (1) (Helmink et al, 2020), while another used gene sets to identify the presence of activated, immature and memory B‐cells and more rarely, plasma cells in melanomas (Cabrita et al, 2020).…”
Section: Phenotype Of B‐cells Infiltrating Melanomamentioning
confidence: 99%
“…The TME consists of non-cellular components such as the extracellular matrix and signalling molecule types and non-tumour cell components such as epithelial cells, smooth muscle cells and immune cells in the tumour ecological niche, and Zhang’s study found that crosstalk between tumour and non-tumour cells played an active role in regulating cancer development and treatment response ( Zhang et al, 2020 ). In recent years, with the development of targeted therapies and immunotherapy, some progress has been made in the treatment of malignant SKCM ( Emens et al, 2017 ; Zaremba et al, 2020 ; Korn et al, 2021 ), such as immune checkpoint inhibitors ( Herbst et al, 2019 ), peripatetic cell therapy and tumour vaccines ( Qi et al, 2015 ), which have achieved better efficacy in clinical trials, bringing new hope for the treatment of SKCM patients, in which tumour-infiltrating immune cells are expected to be a new prognostic marker ( Goeppert et al, 2013 ; Kirilovsky et al, 2016 ), While studies in zebrafish by Elena Gómez-Abenza et al showed that SPINT1 can try to control changes in the cellular immune microenvironment (TME) of SKCM ( Gómez-Abenza et al, 2019 ), Min Yan et al (2021) . Actually pointed to a unique role for T cells in SKCM based on single-cell sequencing results.…”
Section: Introductionmentioning
confidence: 99%